From the “Eumenides” to “Ajax”: The Tragedy of International Criminal Law - Dickson, Tiphaine L. (Sociološki pregled, 2019)
This article examines mainstream and critical approaches to international criminal law, focusing on not only their metaphorical myth-making regarding the legal legitimacy and jurisdictional origins of the ad hoc bodies, but on a peculiar instance of outright reliance on Greek theater to celebrate the inﬂuence of the Nuremberg precedent. The article then traces the evolution of The Eumenides over time in Athenian literature, emphasizing the relation between the early optimism born of the jury trial and the darker undertones that emerge as Athens’ imperial adventures take their toll, as seen in Sophocles’ Ajax and then in Tucydides’ account of the Peloponnesian wars.
Keywords: Legalism; Jury trials; The Eumenides; History of International Criminal Law; Robert Jackson; Nuremberg; International criminal law